Analisis Faktor Kunci dalam Pembuatan Strategi Pengendalian Beban Bunga Operasional - Putri Agustin; Prof. Dr. Nurul Huda, SE. MM. MSi M.Hum; Muhammad Akhyar Adnan, PhD, MBA, SE, AK, CA, CRP, CIB; Muhammad Feriyan Al Banjari (Journal of Economics and Business Aseanomics, 2025)
This study aims to identify the key factors that need to be prioritized in strategies for reducing interest expenses in order to align with budget targets. Interest expenses must be managed effectively as they directly affect the company’s profitability. Based on data from the period 2022 to YTD June 2024 of a vehicle sales company, only 13% of the nominal interest expense achieved the target, and only 10% of the ratio of interest expense to revenue was met.This study employs the Interpretive Structural Modelling (ISM) approach to analyze key sub-elements that serve as key factors in formulating strategies to reduce interest expenses. Four elements are analyzed: needs, activities, constraints, and contributing parties.The results indicate that within the elements of needs, constraints, and activities, the key sub-element is collaboration among related departments. For the contributing parties, the key sub-elements are branch managers, administration heads, sales staff, customers, leasing companies, body builders, and vehicle document agency, all of the internal parties fall under the scope of the sales and administration departments.It is concluded that strengthening collaboration between the sales and administration departments is the primary factor that must be prioritized in strategies to reduce interest expenses.